Ultrasound-guided minimally invasive interventions for refractory musculoskeletal pain: a real-world study from an interventional rheumatology unit - Maria Beatriz Paredes-Romero; Martina Steiner; Ana Valeria Acosta; Israel J. Thuissard; Ana Isabel Castillo-Varón; Gabriela Cueva-Nájera; Marco Algarra-San José; Ana Esteban-Vázquez; Tatiana Cobo-Ibáñez; María Liz Romero-Bogado; Laura Trives-Folguera; Cristina Vergara-Dangond; et al. (Frontiers in Medicine, 2026)
Background Chronic musculoskeletal pain represents a global health challenge, with a substantial proportion of patients failing to achieve adequate symptom control despite conventional treatment. Interventional rheumatology units (IRUs) incorporating ultrasound-guided minimally invasive procedures have emerged as a promising strategy for the management of refractory musculoskeletal pain. However, real-world evidence regarding the performance of these units in routine clinical practice remains limited. This study evaluated the effectiveness and safety of an IRU in routine clinical practice. Methods This retrospective, observational, single-center study included consecutive patients with chronic musculoskeletal pain refractory to conventional treatment, who underwent ultrasound-guided interventions at an IRU between April 2023 and February 2026. Procedures were categorized as myofascial infiltrations, shoulder procedures, erector spinae plane block, and a miscellaneous group of other procedures. The primary outcome was a clinically meaningful pain reduction, defined as a reduction of at least 2 points on the Numerical Rating Scale (NRS) at the first post-procedure follow-up visit. Results A total of 170 patients (77.6% women; median age 61 years) were included. Overall, 125 of 170 patients (73.5%) achieved the primary endpoint, with no significant differences across procedural groups. Median NRS decreased from 7.0 [IQR, 7.0–8.0] to 3.0 [IQR, 2.0–6.0] at follow-up, corresponding to a median reduction of 4.0 points (IQR, 1.0–6.0; p < 0.001). Two minor adverse events (1.2%) were recorded, and 30 patients (17.6%) required repeat procedures. In multivariable logistic regression analysis, a higher baseline NRS score was the only independent predictor of a clinically meaningful response (OR 1.74, 95% CI, 1.30–2.34; p < 0.001). Overall, 50 patients (29.4%) required referral to another specialty, although no baseline clinical variable independently predicted this outcome. Overall, 50 patients (29.4%) required referral to another specialty, although no baseline clinical variable independently predicted this outcome; the remaining 70.6% were managed or discharged by the IRU. Conclusion Ultrasound-guided minimally invasive procedures performed within an IRU were associated with high rates of clinically meaningful pain reduction, and a favorable safety profile in patients with chronic musculoskeletal pain. These findings suggest that IRUs may have a role within multidisciplinary pain management pathways, although prospective controlled studies are needed to confirm these results.